Zorotypus pecten, a new species of Zoraptera (Insecta) from mid-Cretaceous Burmese amber - Mashimo, Yuta; Müller, Patrick; Beutel, Rolf G. (Zootaxa, 2019)
A new species of the order Zoraptera, Zorotypus pecten sp. n., is described from mid-Cretaceous Burmese amber. It is tentatively assigned to the subgenus Octozoros based on 8-segmented antenna. A Gondwanan origin for Zoraptera is discussed based on the geographic distribution of extant and fossil zorapterans.